It is probably easiest to divide by the coefficient of x^2 first. It may also be helpful to put the constant term on the right side of the equal sign.

2x^2 + 11x - 6 = 0

x^2 + (11/2)x - 3 = 0

x^2 + (11/2)x = 3

Now, we complete the square by adding the square of half the x coefficient.

X^2 + (11/2)x +

Consult your text or teacher to see what final form the answer should have.

Taking the square root, we have

x + 11/4 = ±13/4

x = (-11 ± 13)/4

x = 1/2, or x = -6

Thus, the equation can be factored as

(x - 1/2)(x + 6) = 0

We can "rationalize" this by multiplying both sides by 2.

(2x - 1)(x + 6) = 0

2x^2 + 11x - 6 = 0

x^2 + (11/2)x - 3 = 0

x^2 + (11/2)x = 3

Now, we complete the square by adding the square of half the x coefficient.

X^2 + (11/2)x +

**(11/4)^2**= 3 +**(11/4)^2**(x + 11/4)^2 = 3 + 7 9/16**(x + 11/4)^2 = 10 9/16**= 169/16 = (13/4)^2Consult your text or teacher to see what final form the answer should have.

Taking the square root, we have

x + 11/4 = ±13/4

x = (-11 ± 13)/4

x = 1/2, or x = -6

Thus, the equation can be factored as

(x - 1/2)(x + 6) = 0

We can "rationalize" this by multiplying both sides by 2.

(2x - 1)(x + 6) = 0